Non-COVID area of a tertiary care hospital: A major source of nosocomial COVID-19 transmission - Mahendra K Meena; Mahendra Singh; Prasan K Panda; Mukesh K Bairwa (Wolters Kluwer Medknow Publications, 2020)
COVID-19 pandemic has spread to all corners of the world where infection control measures are being implemented. There is now a resurgence of the disease in health care facilities with documented in-hospital transmission and cases becoming positive in areas designated to cater for COVID-19 negative patients. We encountered such an event at our institution where fourteen patients (including health care workers) in the non-COVID zone were found to be COVID-19 positive. This highlights the loopholes in the system and the need for better and systematic infection control measures in hospitals that deal with infectious diseases with high infectivity. Findings also suggests the failure of government's criteria for suspected COVID-19 cases, and therefore needs a rethinking. Keywords: